SAH guided spatial split partitioning for fast BVH construction - Ganestam, Per; Doggett, Michael (Computer graphics forum, 2016)
We present a new SAH guided approach to subdividing triangles as the scene is coarsely partitioned into smaller sets of spatially coherent triangles. Our triangle split approach is integrated into the partitioning stage of a fast BVH construction algorithm, but may as well be used as a stand alone pre‐split pass. Our algorithm significantly reduces the number of split triangles compared to previous methods, while at the same time improving ray tracing performance compared to competing fast BVH construction techniques. We compare performance on Intel's Embree ray tracer and show that BVH construction with our splitting algorithm is always faster than Embree's pre‐split construction algorithm. We also show that our algorithm builds significantly improved quality trees that deliver higher ray tracing performance. Our algorithm is implemented into Embree's open source ray tracing framework, and the source code will be released late 2015.